2016
DOI: 10.1002/2015gb005167
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term P weathering and recent N deposition control contemporary plant‐soil C, N, and P

Abstract: Models are needed to understand how plant-soil nutrient stores and fluxes have responded to the last two centuries of widespread anthropogenic nutrient pollution and predict future change. These models need to integrate across carbon, nitrogen, and phosphorus (C, N, and P) cycles and simulate changes over suitable timescales using available driving data. It is also vital that they are constrainable against observed data to provide confidence in their outputs. To date, no models address all of these requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 112 publications
1
66
0
Order By: Relevance
“…The weathering extent, acidity, and clay and sand content of soil are in part determined by the parent material (Acosta et al., ). Soil parent materials can affect soil organic C retention and soil nutrient availability, as well as strongly modulate the relationship between N and P limitations under different global change regimes (Davies et al., ; Augusto et al., ). The drastically different temporal responses of soil C‐N‐P derived from different parent materials in our study may also be driven by the strong control of soil nutrient supply (such as P) by parent materials (Tables S11 and S12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weathering extent, acidity, and clay and sand content of soil are in part determined by the parent material (Acosta et al., ). Soil parent materials can affect soil organic C retention and soil nutrient availability, as well as strongly modulate the relationship between N and P limitations under different global change regimes (Davies et al., ; Augusto et al., ). The drastically different temporal responses of soil C‐N‐P derived from different parent materials in our study may also be driven by the strong control of soil nutrient supply (such as P) by parent materials (Tables S11 and S12).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this strong stoichiometry, studies conducted in experimentally manipulated ecosystems have demonstrated the decoupling of C, N, and P cycles due to global change drivers (Sardans, Rivas‐Ubach, & Peñuelas, ; Sardans et al., ; Yuan & Chen, ; Yue et al., ). In terrestrial ecosystems, the biogeochemical cycles of C, N, and P in the natural environment are primarily determined by the soil parent material and the degree of soil weathering (Acosta, Martínez‐Martínez, Faz, & Arocena, ; Augusto, Achat, Jonard, Vidal, & Ringeval, ; Davies et al., ; Vitousek, Porder, Houlton, & Chadwick, ), mediated by plants and microorganisms (Lang et al., ; Sinsabaugh et al., ; Vitousek, Menge, Reed, & Cleveland, ), and shaped by climate (Chen, Li, & Yang, ; Delgado‐Baquerizo et al., ; Tan & Wang, ). Disentangling the role of these factors in regulating temporal feedback of ecosystem to environmental change could improve predictions of ecosystem responses to future global change (Beniston, ; Peñuelas & Boada, ; Pretzsch, Biber, Schütze, Uhl, & Rötzer, ; Sundqvist, Sanders, & Wardle, ).…”
Section: Introductionmentioning
confidence: 99%
“…These ecosystems are well-suited to a large-scale evaluation in view of the wide range of N dep (1 st to 99 th percentile 0.2–3.6 gNm −2  a −1 in 2010) and the wealth of data available from repeated soil sampling. The modelling was done by combining the ecosystem model N14CP 13 with a new high-resolution spatio-temporal N dep dataset covering the period since 1750, produced through atmospheric emission, transport and deposition modelling.
Figure 1Maps showing the occurrence of the three semi-natural habitat types (grey scale) and sampling locations (circles). The fractional land cover refers to individual 5 km × 5 km grid cells used in simulation modelling.
…”
Section: Introductionmentioning
confidence: 99%
“…Loss rate constant values were based on previous work, such as the Century model (Parton et al ., ), Mills et al . () and N14CP (Davies et al ., ), with fast (or active), slow and passive pools having mean residence times (MRT) of c . 1, 20 and 1000 years, respectively ( k values of 1, 0.05 and 0.001 year −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…(), and the new model of Abramoff et al . (), hardly mention nitrogen (N) and phosphorus (P), and although both N and P are included in Century, ECOSSE and N14CP (Davies et al ., ), they are forced to follow C. Consequently, the important role of N in SOM stability (Knicker, ) is disregarded, and the same might apply also to P. That N and P may provide valuable modelling constraints is shown by the recently demonstrated systematic relations involving C, N, P and sulphur (S) in SOM (Tipping et al ., ). An important finding was that N:C, P:C and S:C ratios are largest at small C concentrations, where soil mineral matter is most dominant, leading to the conclusion that mineral matter selectively adsorbs organic molecules that on average are rich in N, P and S, in accord with ideas advanced by Kleber et al .…”
Section: Introductionmentioning
confidence: 99%